Study of the Mechanism by Which Curcumin Cooperates with Sestrin2 to Inhibit the Growth of Pancreatic Cancer. (1st July 2021) - Fu, Haotian; Ni, Xiaofeng; Ni, Fubiao; Li, Ding; Sun, Hongwei; Kong, Hongru; Shan, Yunfeng; Dai, Shengjie
Abstract : Background . Pancreatic carcinoma is a malignant tumor with a high fatality rate, and the increased resistance of pancreatic carcinoma to chemotherapy has become a difficult problem in clinical practice. Hence, it is imperative to develop an effective treatment for pancreatic cancer. Sestrins are a class of stress-induced proteins that have antioxidation functions, regulating cell growth and metabolism. Curcumin is a natural pigment isolated from turmeric. Several studies have also suggested that this molecule has multiple pharmacological effects, such as anti-inflammatory, antioxidant, and antitumor effects. However, there are insufficient studies on curcumin cooperating with the sestrin family to inhibit tumors, and the mechanism is still unclear. Our aim was to observe the potential anticancer effects of curcumin combined with the sestrin family on pancreatic carcinoma and probe its possible molecular mechanisms. Methods . Lentiviral infection, real-time fluorescence quantitative PCR assays, Cell Counting Kit-8 assays, real-time cell analysis technology, colony formation assays, wound healing assays, Transwell invasion assays, protein extraction, and western blots (WBs) were used to evaluate the effect of curcumin combined with sestrin2 on the proliferation, invasion, and migration of pancreatic carcinoma cells. Results . The results revealed that curcumin cooperated with sestrin2 to significantly suppress pancreatic cancer. In addition, we determined that sestrin2 cooperated with curcumin to inhibit pancreatic cancer by specifically targeting Nrf2/Keap1/HO-1/NQO-1. Conclusion . These findings clarify that curcumin-mediated synergistic targeting of sestrin2 is a potentially valuable treatment for pancreatic cancer.